2007
DOI: 10.1186/1476-4598-6-42
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and role of p21cip/waf1 and p27kip1 in TNF-α-induced inhibition of proliferation in human glioma cells

Abstract: Background: The role of TNF-α in affecting the fate of tumors is controversial, while some studies have reported apoptotic or necrotic effects of TNF-α, others provide evidence that endogenous TNF-α promotes growth and development of tumors. Understanding the mechanism(s) of TNF-α mediated growth arrest will be important in unraveling the contribution of tissue associated macrophages in tumor resistance. The aim of this study was to investigate the role of Cyclin Dependent Kinase Inhibitors (CDKI) -p21 cip/waf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…12 Overexpression of p21 but not p27 prevents proliferation of human glioma cells. 31 These results indicate that p21 may be a major regulator of p53-induced cell growth arrest in VSMCs, as well as in certain cancer cells. The observations gleaned from the present study indicate that the upregulation of p21 mediated by activated p53 results in the suppression of cyclin E and cyclin D (Figure 2D), which leads to the inhibition of the formation of cyclin D/E and cyclin-dependent kinase (CDK) complexes.…”
Section: Discussionmentioning
confidence: 82%
“…12 Overexpression of p21 but not p27 prevents proliferation of human glioma cells. 31 These results indicate that p21 may be a major regulator of p53-induced cell growth arrest in VSMCs, as well as in certain cancer cells. The observations gleaned from the present study indicate that the upregulation of p21 mediated by activated p53 results in the suppression of cyclin E and cyclin D (Figure 2D), which leads to the inhibition of the formation of cyclin D/E and cyclin-dependent kinase (CDK) complexes.…”
Section: Discussionmentioning
confidence: 82%
“…The role of TNF-α is controversial; some investigations have proved apoptotic or necrotic effects of TNF-α, while others furnished evidence that endogenous TNF-α activates cellular growth and tumor progression [19]. …”
Section: Resultsmentioning
confidence: 99%
“…35 We in our earlier studies showed that p21 functions as an inhibitor of cell proliferation in LN-18 glioma cells. 36 It is demonstrated that various transformation events induce downregula- tion of p21, followed by activation of AKT or ERK2, which interacts and phosphorylates p21, thereby promoting p21Cip1 nucleo-cytoplasmic translocation and ubiquitin-dependent degradation, resulting in cell cycle progression. 37 Several studies suggest that localization of p21 (Cip1) to the cytoplasm in transformed cells contributes to pathways that favor not only cell proliferation but also cell motility, thereby contributing to invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%